Aplikasi Perancangan Website Kamben Bali Menggunakan Metode User Centered Design - Muliawan, I Ketut Agus Pranata; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
In the current era of technological development, many activities are carried out online, be it meetings, transportation orders, ordering food and drinks, and even education. Many young people today do not know the fabric of Balinese kamben. Therefore, the existence of a Balinese kamben website designed to expand knowledge from the website through internet connectivity that is connected continuously can facilitate the search for Balinese kamben fabrics. This study aims to determine whether the system design that will be designed can help users in searching for Balinese kamben cloth. This system will run on the web and use javascript as a programming language. The User-Centered Design method is used in designing the Bali kamben application website to conduct user-centered testing in a questionnaire involving respondents or users along with a Black Box to ensure the system runs according to its function.